Increasing Winter Wheat Grain Yield by Replicating the Management Adopted in High-Yielding Commercial Fields - L. Ryan; L. A. Haag; J. D. Holman; R. P. Lollato (Kansas Agricultural Experiment Station Research Reports, 2022)
Large winter wheat yield gaps between farmer yields and yield potential in the southern Great Plains indicate the need to improve recommendations of best management strategies to profitably bridge this gap. Many studies have been completed on individual management factors pre-determined by the individual researcher, but we are not aware of studies comparing combination of practices that producers are currently using, which would be more relevant for real-world scenarios. Our objective was to determine the yield gains resulting from management intensification using combination of practices currently adopted in commercial wheat fields. Four management intensities (i.e., Low, Average, High, and Top) were derived from a survey of 656 commercial fields, and replicated in trials conducted in four and six locations in western and central Kansas. Management intensities were tested factorially on two adapted varieties. Grain yield in central Kansas ranged from 45.5 bu/a in the Low management intensity to 69.3 bu/a in the High and Top intensities, with the Average management increasing yields by 30% as compared to the Low intensity, and the High management increasing yields 18% from the Average. The variety WB4269 outyielded Zenda (63.2 and 58.7 bu/a) across central environments. In western Kansas, there was a significant variety by management interaction, where wheat yield increased from the Low and Average intensities to the High and Top intensities (72.8–78.9 to 90.7–96.0 bu/a). The WB-Grainfield and KS Dallas varieties produced similar yields in the western environments. Using similar management practices as the producers with high-yield results in central and western Kansas narrowed the yield gap, and further increases in management intensification were not warranted. Variety selection played an important role either by increasing attained yields or by interacting with management practices.
Keywords: intensive management; fungicide; fertility; plant population; on-farm research